Niepokalane Poczęcie Maryi a miłosierdzie Boże - Warzeszak, Józef (Warszawskie Studia Teologiczne, 2019)
The purpose of the article is to demonstrate that there is a mutual relationship between the Immaculate Conception of Mary and Divine Mercy. The author asserts that the act of creating Mary free from original sin was God’s act of mercy in the context of her calling to participate in the work of redemption, in keeping her constantly free from personal sins. In addition, Mary’s sanctity is a gift of Divine Mercy for sinners who can have recourse to her. God also showed his mercy by giving Mary to people in order to protect them against Satan’s attacks, as Satan never had power over her.